Arbuscular Mycorrhizal Colonisation Modifies the Water Relations of Young Transplanted Grapevines (Vitis) - van Rooyen, M.; Valentine, A.; Archer, E. (South African Journal of Enology and Viticulture, 2017)
The effect of arbuscular mycorrhizal (AM) colonisation on the alleviation of transplantation shock in young grapevines was investigated. One-year-old grapevines (Sauvignon blanc on Richter 99), colonised with Glomus etunicatum (Becker and Gerdemann), were cultivated in an atmosphere-controlled tunnel. Water relations, leaf photosynthetic parameters and growth characters were evaluated. AM colonisation enhanced the photosynthetic performance of host plants, but had no influence on biomass and mineral nutrition of the transplanted hosts. The increased photosynthetic rates of the AM plants were related to improved water relations. Stomata] conductance, transpiration rate and midday xylem water potential were higher in the AM hosts during the transplanted period. These results indicate that AM inoculation can influence the water relations of transplanted grapevine rootstocks, thereby improving photosynthetic performance and potential survival during the initial growth stages of the host plants.